Sd-021, derivatives of decursin, inhibits tumorigenesis in NSCLC by inhibiting the EGFR/STAT3 signaling pathway - Hyun-Ha Hwang; Jeong-Hui Je; Hyeong-Chan Lee; Ji-Sung Yoo; Taehyoun Kim; Jung Hwan Choi; Jin Won Hong; Hae-In Lim; Ga Yoon Kim; Yun-Beom Sim; Kwang-Jin Cho; Eun-wook Choi; et al. (Scientific Reports)
Abstract Lung cancer, particularly non-small cell lung cancer (NSCLC), remains a significant challenge in oncology despite advances in targeted and immune-based therapies. NSCLC accounts for approximately 85% of all lung cancer cases, with five-year survival rates ranging from 4 to 17%, depending on disease stage and regional factors. Chemotherapy resistance remains a major hurdle, contributing to poor patient prognosis. This study explores the therapeutic potential of Sd-021, a novel decursinol derivative, compared to its parent compound, decursin, within various NSCLC cell lines. Our results reveal that Sd-021 demonstrates enhanced anticancer activity, highlighted by a more significant reduction in cell viability, increased induction of apoptosis, and more pronounced cell cycle arrest. Notably, Sd-021 shows increased inhibition of the EGFR/STAT3 signaling pathway in EGFR wild-type cell lines, including A549, H460, and H1299 cells. Moreover, in vivo experiments employing a subcutaneous xenograft mouse model reveal that Sd-021 reduces tumor volume with minimal systemic toxicity, as indicated by histopathological assessments revealing reduced tumor proliferation and heightened apoptosis. The minimal toxicity of Sd-021 offers reassurance regarding its safety for potential clinical applications. In conclusion, these findings highlight the promise of Sd-021 as a therapeutic agent against NSCLC.